Effective learning tool using AR for knee and foot anatomy based on CT images 3D reconstruction - Liew, Set Lee (2020)
Anatomy is the branch of biological science in medical education that focus on structured part of any living beings. While human body anatomy is an important chapter in any Biology subject for students of secondary and post-secondary education in Malaysia. Traditional methods and materials of learning human body anatomy usually available in the form of textbooks with pictures and photos and artificial anatomy mannequins. There are still not enough and hard to help students in understanding it with actual and accurate knowledge and images about our human body anatomy. This is because students are hard to imagine the reality structure of human anatomy body part and lack of interaction through the 2D images on the textbooks. Although there are artificial anatomy mannequins available and provided to access by the students in the school or university, it is limited in number of the mannequins due to its expensiveness and thus students need to queue to access the mannequins among the class. Besides, students are not able to access the artificial anatomy mannequins when they study and do revision out of the school time. Moreover, some of the students are facing difficulties in understanding 2D images on the textbooks as well, making them hard to understand and acquire the knowledge as fast as possible in learning the structure of human anatomy body part. Therefore, a project titled “Effective Learning Tool Using AR for Knee and Foot Anatomy Based on CT Images 3D Reconstruction” will be study and develop to overcome those issues and problems. An AR learning knee and foot anatomy application will be developed through medical 3-dimensional(3D) reconstruction based on medical images. Incremental development model will be involved in this project. The purpose of this project is to provide an alternative learning method for student to study the complex structures of human body anatomy in more effective and more interactive way with the mobile computing platform.